1995
DOI: 10.1139/f95-052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3,3′,4,4′-tetrachlorobiphenyl on the dynamics of vitamin A in brook trout (Salvelinus fontinalis) and intestinal retinoid concentrations in lake sturgeon (Acipenser fulvescens)

Abstract: A single i.p. injection of 5 pg 3,3',4,4'-tetrachlorobiphenyl (TCBP)/g body mass in adult brook trout (IFkB&ve&inus fontinadis) resulted in decreased (p < 0.0001) growth rate despite pair feeding. Plasma retinol decreased (p < 0.0037). Intestinal retinyl palmitate (RP) and 3,4-dehydroretinyl palmitate (DRP) concentrations decreased in TCBP-injected males (RP, p < 0.0143; DWP, p < 0.0009), whereas retinoid levels did mot decrease significantly in TCBP-injected females. The RP:DRP ratio in trout liver increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
13

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 35 publications
2
20
0
13
Order By: Relevance
“…Decreased liver retinoid stores had been previously documented in adult white sucker and in lake sturgeon (Acipenser fulvescens) captured near Montreal (Spear et al, 1992;Branchaud et al, 1995). Lower levels of intestinal retinoids (retinyl palmitate and dehydroretinyl palmitate) were also found in lake sturgeon captured near Montreal (Ndayibagira et al, 1994). When compared to a reference population at a relatively uncontaminated site on the same river, laboratory-raised larvae from fish collected at the Montreal site had very low hepatic stores of retinol and retinyl palmitate.…”
Section: Retinoid Alterationsmentioning
confidence: 65%
See 1 more Smart Citation
“…Decreased liver retinoid stores had been previously documented in adult white sucker and in lake sturgeon (Acipenser fulvescens) captured near Montreal (Spear et al, 1992;Branchaud et al, 1995). Lower levels of intestinal retinoids (retinyl palmitate and dehydroretinyl palmitate) were also found in lake sturgeon captured near Montreal (Ndayibagira et al, 1994). When compared to a reference population at a relatively uncontaminated site on the same river, laboratory-raised larvae from fish collected at the Montreal site had very low hepatic stores of retinol and retinyl palmitate.…”
Section: Retinoid Alterationsmentioning
confidence: 65%
“…Exposure of adult brook trout (Salvelinus fontinalis) to a single intraperitoneal injection of PCB 77 decreased plasma retinol and intestinal retinoids in males (Ndayibagira et al, 1994). Oral exposure to the coplanar PCB 126 (3, 3Ј,4,4Ј,5-pentachlorobiphenyl) resulted in decreased liver retinoids in lake trout (Salvelinus namaycush) (Palace and Brown, 1994).…”
Section: Retinoid Alterationsmentioning
confidence: 99%
“…Among larvae raised in an artificial stream, prevalence of fin deformities was highly significantly greater in the progeny of lake sturgeon sampled in Des Prairies River (6.3%) compared with the progeny of lake sturgeon from the reference site (1.7%) [Doyon et al 1999]. Concentrations of liver and intestine retinoids were also found to be significantly lower (as much as 40 times lower) in the Des Prairies River sample (Doyon et al 1998(Doyon et al , 1999Ndayibagira et al 1995).…”
Section: Limiting Factors and Threatsmentioning
confidence: 88%
“…As the lake sturgeon is a benthic species, fish often are exposed to high contaminant loads. Individuals exposed to systems with high contaminant loads compared to noncontaminated systems had lower retinoids than fish in non-contaminated systems (Ndayibagira et al 1995).…”
Section: Limiting Factors and Threatsmentioning
confidence: 89%
“…Therefore, decreased RE contents in the intestine would cause fewer REs to be released into the blood circulation for liver storage. A previous study showed that the injection of polychlorinated biphenyls (PCBs) caused a significant decrease of intestinal retinyl ester contents in brook trout (Salvelinus fontinalis) (Ndayibagira et al, 1995).…”
Section: Discussionmentioning
confidence: 99%